2012
DOI: 10.3750/aip2012.42.4.01
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the feeding ecology of selected fish species from the Okavango River delta, Botswana

Abstract: Mosepele K., Mosepele B., Wolski P., Kolding J. 2012. Dynamics of the feeding ecology of selected fish species from the Okavango River delta, Botswana. Acta Ichthyol. Piscat. 42 (4): 271-289.Background. This study contributes to the understanding of the potential impact of changes in flooding patterns and (potential) fish production as a consequence of upstream developments in floodplain systems. Therefore, stomachs of eight fish species from the Okavango Delta were analysed to evaluate the feeding ecology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Their study revealed that most fish species from the delta are opportunistic feeders whose diet is changed seasonally regulated by the seasonal flood pulse. In fact, the feeding rate of some fish species is driven by changes in either mean depth or discharge [80]. This study [80] revealed that fish diet varied between terrestrial and aquatic sources, depending on the seasonal hydrograph.…”
Section: Biology and Ecology Of Fisheriesmentioning
confidence: 86%
See 4 more Smart Citations
“…Their study revealed that most fish species from the delta are opportunistic feeders whose diet is changed seasonally regulated by the seasonal flood pulse. In fact, the feeding rate of some fish species is driven by changes in either mean depth or discharge [80]. This study [80] revealed that fish diet varied between terrestrial and aquatic sources, depending on the seasonal hydrograph.…”
Section: Biology and Ecology Of Fisheriesmentioning
confidence: 86%
“…The majority of fish species are insectivores (Table 1), which highlights the importance of insects/ aquatic macroinvertebrates in fish biomass production in the delta. This notwithstanding, the delta's fish species have a relatively plastic feeding behavior [79,80], because of the dynamic nature of the system. Schilbe intermedius is one of the dominant species in the delta's fish community [79,81], possibly due to its opportunistic feeding ecology [79,81], where it also feeds on terrestrial food items, driven by the seasonal flood pulse [80].…”
Section: Biology and Ecology Of Fisheriesmentioning
confidence: 99%
See 3 more Smart Citations